AGRIBISNIS HORTIKULTURA: PELUANG DAN TANTANGAN DALAM ERA PERDAGANGAN BEBAS - IRAWAN, BAMBANG (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003, 2012)
During two last decades food trade in the world market was shift to horticultural products such as fruits and vegetables. Household consumption of the products also tends to increase in domestic market due to the increase of income per caput, induced by economic growth. The two tendencies reveals that market of horticultural products will increase in the future both in domestic and world markets, and barier of entry to the market will be eliminated in the era of trade liberalisation. It is true that Indonesia had a surplus in the trade of horticultural products, comes particularly from fruits trade, but this surplus is continuously decreasing resulted from decrease of competitiveness of local agribusiness compared with those from Africa and Southern America countries particularly. To increase competitiveness of local agribusiness, future development of horticulture sector should be focused on three efforts : (1) Development of vertically integrated agribusiness so that horticultural agribusiness has capability to respond market demand effectively. This effort can be implemented through development of partnership business system between input trader, farmer and output trader. (2) Price stabilization of horticultural products, which can be taken by establishment of regional agribusiness institution across producer regions. The main task of the institution is to regulate supply quantity of overall producer adjusted to market requirement. (3) Facilitation of post harvest infrastructure to farmers in order to retard degradation of product quality and to improve bargaining position of farmers in the price formation at producer market.
Keywords: Trade Liberalization, Horticulture Products, Consumption, International Trade, Competitiveness of Agribusiness.